Managing Across Borders: An Empirical Test of the Bartlett and Ghoshal [1989] Organizational Typology - Leong, Siew Meng; Tan, Chin Tiong (Journal of International Business Studies, 1993)
This paper reports an empirical test of the Bartlett and Ghoshal [1989] organizational typology. Some 131 senior executives of corporations with worldwide operations classified their organizations as being multinational, global, international, or transnational in nature and evaluated their organizations' configuration of assets and capabilities, role of overseas operations, and development and diffusion of knowledge. Results provide partial support for the typology. As expected, transnational corporations were least frequently reported by the respondents. The hypothesized practices associated with multinational and global organizations were more consistent with the typology's predictions relative to those of the international and transnational types.